Changements d’occupation du sol et leurs impacts climatiques au Mato Grosso, Brésil - Vincent Dubreuil; Camille Delahaye; Adeline Le Strat (Confins)
Changes in land cover (deforestation, urbanization) in the Brazilian Amazon have a strong effect on the temperatures at local scale. This paper compares the temperatures of July 2007 between the urban area, the area deforested for pasture and forest in the region of Alta Floresta (Mato Grosso). The climatic changes are marked during the day but especially in the beginning and the end of the day (with significant differences between temperatures of 2 ° C to 4.3 ° C between the forest sector and the city center). The cleared area is generally warmer than the forest area. A second part of the paper concerns the study of the urban heat island for three cities of Mato Grosso: Rondonopolis, Sorriso and Sinop. Observations made by the mobile transect method in July 2009 show that temperatures are higher in dense urbanized areas than in residential areas. The effect of urban heat island is particularly well marked, especially at night and during the dry season but, locally, the role of topography and urban parks is also very sensitive (cool areas).